Control of apple snail with copper chelate and ozonated water in rice cultivation at field level - Llerena Hidalgo, Angel Bernardo (Revista Mexicana de Ciencias Agrícolas, 2022)
The pest that has caused the most problems in rice (Oriza sativa L.) in recent years is the apple snail, Pomacea canaliculata (Lamarck); this pest is considered among the 100 worst invasive species in the world. The present work is an experimental trial at the field level where different doses of copper chelate and ozonated water were applied to control the apple snail in rice cultivation; for which a randomized complete block design (RCBD) was used, with five treatments, including the control and four repetitions. The experimental site was located on a farm in the Salitre canton, in the Guayas province, Ecuador, with tropical climate. The mortality rate of the snails against the proposed treatments was evaluated. Treatment T4, which corresponded to the dose of 2 L ha-1 of copper chelate mixed with ozonated water with a concentration of 2 ppm, was the treatment were the best apple snail control was observed, resulting in 94% mortality.
Keywords: apple snail; copper; ozonated water